Sleep Quality Associated With Different Work Schedules: A Longitudinal Study of Nursing Staff. (July 2017) - Niu, Shu-Fen; Miao, Nae-Fang; Liao, Yuan-Mei; Chi, Mei-Ju; Chung, Min-Huey; Chou, Kuei-Ru
Purpose: To explore the differences in sleep parameters between nurses working a slow, forward rotating shift and those working a fixed day shift. Method: A longitudinal parallel-group comparison design was used in this prospective study. Participants (female) were randomly assigned to a rotating shift or a fixed day shift group. Participants in the rotating shift group worked day shift for the first 4 weeks, followed by evening shift for the second and night shift the third. Those in the day shift group worked day shift for all 12 weeks. Each kept a sleep diary and wore an actigraph (actigraph data were used to calculate total sleep time [TST], sleep onset latency [SOL], wake after sleep onset [WASO], and sleep efficiency [SE]) for 12 days, from Workday 1–4 in each of Weeks 4, 8, and 12. Results: TST in nurses working evening rotating shift was higher than that for those working the day or night rotating shift and fixed day shift. WASO was significantly longer on Day 2 for rotating shift participants working evening versus day shift. SOL and SE were significantly shorter and lower in rotating shift nurses working night versus both day and evening shifts. Conclusions: A comprehensive understanding of the sleep patterns and quality of nurses with different work shifts may lead to better management of work shifts that reduces the influence of shift work on sleep quality.